Application of dendrimer modified halloysite nanotubes as a new sorbent for ultrasound-assisted dispersive micro-solid phase extraction and sequential determination of cadmium and lead in water samples. Issue 7 (2nd June 2016) - Krawczyk, Magdalena; Akbari, Somaye; Jeszka-Skowron, Magdalena; Pajootan, Elmira; Fard, Farnaz Shahamati
Abstract : A preconcentration procedure for cadmium and lead using dendrimer modified HNTs was developed prior to its sequential determination by HR-CS GFAAS. Abstract : The combination of ultrasound-assisted dispersive micro-solid phase extraction (USA DMSPE) and high-resolution continuum source graphite furnace atomic absorption spectrometry (HR-CS GFAAS) was developed for the sequential determination of cadmium and lead in water samples. During the preconcentration step, dendrimer modified halloysite nanotubes (HNTs-G3) were used as a solid sorbent. Fourier transform infrared (FTIR) spectroscopy was used to characterize HNTs during the modification steps. HNTs-G3 were dispersed in water samples containing trace elements to be determined. After the sorption, the aqueous samples were separated by centrifugation. Then, the metal loaded HNTs-G3 were suspended using a small volume of deionized water and introduced into an atomizer. The main extraction and detection parameters were investigated. The concentration limits of detection were 0.5 and 10 ng L −1 for Cd and Pb, respectively. The preconcentration factors achieved for Cd and Pb were 46 and 41, respectively. The relative standard deviations (RSDs) were 4% and 5% for Cd and Pb, respectively. The accuracy of this method was validated by analyses of NIST SRM 1643e (Trace Elements in Water), TMRAIN-04 (Rainwater) and ERM – CA011b (Hard Drinking Water). The measured element contents in these reference materials were in satisfactory agreement with the certified values according to the t -test for a 95% confidence level. The proposed method has been successfully applied to the determination of cadmium and lead in six different water samples (seawater, lake water, river water, stream water, mine water and tap water).